The Influence of the Work Environment, Work Stress and Work Motivation on Employee Performance at PT. Indolakto - Sahlani Pratiwi, Theysa; Praptasari, Mutiara; Rugayah, Siti (Politeknik Siber Cerdika Internasional, 2024)
Work-related stress among employees can have negative impacts on their productivity and well-being. Some contributing factors to work-related stress involve excessive workload, tight deadlines, and interpersonal conflicts. Its effects encompass subjective, behavioral, cognitive, physiological, and health aspects, leading to decreased productivity and job dissatisfaction. This research aims to analyze the influence of the work environment and work-related stress on employee performance at PT. Indolacto. The causal research method involves the entire employees of PT. Indolakto (population of 116 people) with a research sample of 90 individuals. The analysis employs parametric statistics with Likert scales for variable measurement. The study focuses on the work environment, work-related stress, and work motivation as independent variables, while employee performance serves as the dependent variable. The research results are expected to contribute to understanding the factors affecting employee performance, providing insights for company improvement, and enhancing the researcher's capability in addressing issues in this field. The information from this study can serve as a foundation for the company's future improvements and developments.